2019
DOI: 10.1002/ange.201910053
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Driven Janus Microvehicles in Biological Media

Abstract: Alight-driven multifunctional Janus micromotor for the removal of bacterial endotoxins and heavy metals is described. The micromotor was assembled by using the biocompatible polymer polycaprolactone for the encapsulation of CdTeo rC dSe@ZnS quantum dots (QDs) as photoactive materials and an asymmetric Fe 3 O 4 patch for propulsion. The micromotors can be activated with visible light (470-490 nm) to propel in peroxide or glucose media by adiffusiophoretic mechanism. Efficient propulsion was observed for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Therefore, researchers have tried different methods to improve the absorption ability and photocatalytic efficiency of VLD-MNM materials. [80] 0.1 1.23 1.33…”
Section: Inorganic Photoactive Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, researchers have tried different methods to improve the absorption ability and photocatalytic efficiency of VLD-MNM materials. [80] 0.1 1.23 1.33…”
Section: Inorganic Photoactive Materialsmentioning
confidence: 99%
“…The CdS quantum dots modified with polypropylenimine tetrahexacontaamine dendrimer generation 5 for the incorporation of fluorescence CdS, as shown in Figure 12(d) . Inspired by this strategy, Pacheco et al reported a visible-light-driven CdTe-Fe 3 O 4 Janus micromotor, which can be used for heavy metal removal and sensing [ 80 ]. The photoresponsive CdTe quantum dots can interact with Hg 2+ , resulting in the cation exchange of Cd 2+ to HgTe.…”
Section: Applicationsmentioning
confidence: 99%
“…2 g/L, ~10 mM), and trace amounts of vitamins and glucose (4.5 g/L, ~25 mM), some of which can be used as reducing agents and, hence, hole extraction fuel to power light-driven microswimmers. 53 Under illumination, the mean speed of the microswimmers in dPBS was 19.0 ± 3.3 µm/s (21% slower than in DI water) and 23.7 ± 2.6 µm/s in DMEM (comparable to DI water), as seen in Figure 2a. The ions present in dPBS (~150 mM) hence only have a relatively small influence on the speed of PHI, whereas the additional components in DMEM do not hamper the efficiency of photocatalytic reactions being responsible for the propulsion (Movie S2).…”
Section: Light-induced Swimming In Different Biological Mediamentioning
confidence: 88%
“…For example, a PCL micromotor encapsulating magnetic nanoparticles and biocompatible QDs can move in serum and blood for the detection of heavy metals and toxins. Biocompatibility assays revealed the full compatibility with the fluids, and the micromotor can be degraded using natural lipases [ 32 ].…”
Section: Jps and Jms: Fabrication Routes And Attributes Pursuedmentioning
confidence: 99%